Implementing Reflection in In-Depth Learning in Social Studies in Elementary Schools: Analysis of the Process and Supporting Factors - Wardatun Nariah; Nasyariah Siregar; Vioni Saputri (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the implementation of reflection in deep learning within the subject of Natural and Social Sciences (IPAS) at SD Negeri 206/IV Kota Jambi, Indonesia, focusing on the implementation process and supporting factors. The study employed a descriptive qualitative approach involving a teacher and fourth-grade students. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings show that reflective practices were carried out through five stages: awareness of learning experiences, conceptual understanding, connecting materials to real-life contexts, awareness of learning strategies, and self-evaluation. The implementation of reflection was supported by active teacher involvement, the use of varied instructional methods, and a conducive learning environment. However, several challenges were identified, including limited instructional time, differences in students’ abilities, and students’ initial lack of understanding of reflective activities. The study concludes that reflection plays an important role in enhancing students’ understanding and engagement in deep learning and supports effective IPAS instruction at the elementary school level.